Determining electric and erosive wearing of conductive tips of welding torch - Абрамов, А.А.; Завгородний, В.В. (Problems of Tribology, 2014)
The paper represents the metods for determining the part of electric and erosive wear in the total amount of wear of conductive tips of welding torch while heating them to the temperature exceeding recrystallization. There is conducted the analysis of total and electric-erosive resistance of the tips made from copper M1, copper E-Cu (Binzel) and chrome-zirconium bronze (Binzel) while joint effect of friction force and electric charges.